Advantages and application of ultrasonic irrigation in endodontics - Abdulwahab, Maha A.; Alghamdi, Lama A.; Alshamrani, Nawaf A.; Alharbi, Khalid M.; Alghamdi, Salem M.; Alshamrani, Amjad M.; Hamouh, Jumanah K.; Qattan, Rajwa M.; Damanhori, Omneya N.; Alzhrani, Renad S.; Alshehri, Mayar A. (International Journal Of Community Medicine And Public Health, 2021)
In the current practice, evidence shows that the currently used irrigant solutions (including sodium hypochlorite combined with and without chlorhexidine or ethylenediaminetetraacetic acid) cannot achieve full cleaning outcomes of the root canal. Accordingly, recent approaches were directed to innovate more efficacious modalities that can overcome the limitations of manual instrumentation and irrigation solutions. In this context, ultrasonic irrigation has been described in the literature as a favorable approach with significantly enhanced outcomes. We have provided evidence regarding the use of ultrasonic irrigation in endodontics. Our findings indicate that passive ultrasonic irrigation is more effective than manual instrumentation in eradicating debris and achieving favorable disinfection. Besides, it has been evidenced that the modality significantly reduces the time to achieve favorable treatment outcomes compared with the traditional approaches. It has been furtherly shown that more favorable outcomes were associated with the combined use of passive ultrasonic irrigation with manual instrumentation. Therefore, it has been suggested that manual instrumentation should be used at the initial phase to achieve adequate preparation, and passive ultrasonic irrigation should be used later on to achieve root canal cleaning.